2019
DOI: 10.1038/s41598-019-55691-w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the fecal microbiome in cats with inflammatory bowel disease or alimentary small cell lymphoma

Abstract: Feline chronic enteropathy (CE) is a common gastrointestinal disorder in cats and mainly comprises inflammatory bowel disease (IBD) and small cell lymphoma (SCL). Both IBD and SCL in cats share features with chronic enteropathies such as IBD and monomorphic epitheliotropic intestinal T-cell lymphoma in humans. The aim of this study was to characterize the fecal microbiome of 38 healthy cats and 27 cats with CE (13 cats with IBD and 14 cats with SCL). Alpha diversity indices were significantly decreased in cats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(125 citation statements)
references
References 68 publications
9
111
0
5
Order By: Relevance
“…[27][28][29][30] 31 2018.8 pipeline as described elsewhere. 32,33 The amplicon sequence variant (ASV) table was created using DADA2, 34…”
Section: Serum Markersmentioning
confidence: 99%
“…[27][28][29][30] 31 2018.8 pipeline as described elsewhere. 32,33 The amplicon sequence variant (ASV) table was created using DADA2, 34…”
Section: Serum Markersmentioning
confidence: 99%
“…In the same way, some members of the Bacteroidetes, especially Bacteroides plebeius which has been associated with remission in humans with inflammatory bowel disease, and Actinobacteria phyla showed a trend towards a decrease abundance in case of CE (Marsilio et al ., 2019). In contrast, representatives of the Enterobacteriaceae and Streptococcaceae families appear to increase in CE‐associated feline faeces coupled with Desulfovibrio spp., which are known to be toxic sulfide producers (Inness et al ., 2007; Marsilio et al ., 2019). Furthermore, various studies, employing different experimental procedures, including 16S rRNA sequencing and fluorescence in situ hybridization (FISH), highlighted that cats with CE generally show a decrease in the relative abundance of the Bifidobacterium genus, a trend that had not been documented for dogs suffering from CE (Inness et al ., 2007; Marsilio et al ., 2019).…”
Section: The Canine and Feline Gut Microbiota And Gi Diseasesmentioning
confidence: 99%
“…However, the administration of probiotics markedly increased the presence of Lactobacillus and Bacteroidetes in constipated cats (Rossi et al, 2017). Using Illumina sequencing, Marsilio et al (2019) revealed a decreased alpha diversity in cats with IBD and small cell lymphoma (SCL) and a significant difference in bacterial communities with a small effect size. Cats with IBD and SCL both displayed a higher abundance of Enterobacteriaceae and Streptococcaceae and a lower abundance of Ruminococcaceae, Turicibacteraceae, Bifidobacterium, and Bacteroidetes (Marsilio et al, 2019).…”
Section: Diseasesmentioning
confidence: 99%
“…Using Illumina sequencing, Marsilio et al (2019) revealed a decreased alpha diversity in cats with IBD and small cell lymphoma (SCL) and a significant difference in bacterial communities with a small effect size. Cats with IBD and SCL both displayed a higher abundance of Enterobacteriaceae and Streptococcaceae and a lower abundance of Ruminococcaceae, Turicibacteraceae, Bifidobacterium, and Bacteroidetes (Marsilio et al, 2019). Microbiota imbalance, often defined as "dysbiosis, " refers to any disturbance of the normal microbial content that can disrupt the symbiotic relationships between microorganisms and the host, potentially leading to the onset of pathologies (Carding et al, 2015).…”
Section: Diseasesmentioning
confidence: 99%